2013
DOI: 10.1371/journal.pone.0049783
|View full text |Cite
|
Sign up to set email alerts
|

The P Body Protein Dcp1a Is Hyper-phosphorylated during Mitosis

Abstract: Processing bodies (PBs) are non-membranous cytoplasmic structures found in all eukaryotes. Many of their components such as the Dcp1 and Dcp2 proteins are highly conserved. Using live-cell imaging we found that PB structures disassembled as cells prepared for cell division, and then began to reassemble during the late stages of cytokinesis. During the cell cycle and as cells passed through S phase, PB numbers increased. However, there was no memory of PB numbers between mother and daughter cells. Examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
76
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 35 publications
(54 reference statements)
3
76
1
Order By: Relevance
“…For instance, microtubule depolymerizing drugs prevent assembly of large stress granules 39,40 and germ granules in early zebrafish embryos, 41 whereas P-bodies become larger, and less mobile. 42,43 Specific dynein and kinesin motor proteins also localize in stress granules, and appear to facilitate assembly and disassembly of stress granules, respectively. 40 Dynein proteins also increase P-body assembly under stress.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, microtubule depolymerizing drugs prevent assembly of large stress granules 39,40 and germ granules in early zebrafish embryos, 41 whereas P-bodies become larger, and less mobile. 42,43 Specific dynein and kinesin motor proteins also localize in stress granules, and appear to facilitate assembly and disassembly of stress granules, respectively. 40 Dynein proteins also increase P-body assembly under stress.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…52,53 O-linked N-acetyl glucosamine, 53 poly (ADP) ribosylation, 54 acetylation, and ubiqutination 39 are also modifications present on specific stress granule components, which have been implicated in stress granule assembly, albeit the mechanisms are not entirely clear. Finally, the phosphorylation of several proteins, including G3BP, 29 TTP, 55 Dcp1, 42,56 Dcp2, 57 and 4E-T 58 alters their localization within, and/or the assembly of their respective granules. In addition, phosphorylation in the prion-like domain of FUS impairs hydrogel formation in vitro.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…Previous studies have indicated roles for Dcp1a in P-body formation, maintenance, and regulation (6,32,33). Dcp1a in P-bodies constantly and quickly exchanges with Dcp1a in the cytoplasmic pool during fluorescence recovery after photobleaching analysis (34).…”
mentioning
confidence: 99%
“…Interestingly, the EVH1 domain of Dcp1a is highly conserved, but the substrate specificity varies across species (42). Recent studies have looked at the status of Dcp1a and P-bodies during stages of the cell cycle and the importance of Dcp1a phosphorylation for its function (32,33,36). These studies have highlighted the importance of Dcp1a phosphorylation in several signaling pathways that affect P-body formation and maintenance.…”
mentioning
confidence: 99%
See 1 more Smart Citation